Rewriting city narratives and spirit: Post-pandemic urban recovery mechanisms in the shadow of the global "black lives matter" movement - Zaheer Allam; David Jones; Can Biyik; Zarrin Allam; Yusra Raisah Takun (Research in Globalization, 2021)
The social media live-broadcasted murder of George Floyd by Minnesota police officers in the United States ignited a national uprising as it highlighted continued discrimination of the African-American community. Amidst the coronavirus pandemic, this fuelled the 'Black Lives Matter' movement and gave way to protests of an unprecedented scale causing havoc in major cities in the United States, with losses tabled in both the public and private sectors. Interestingly, this momentum kindled similar protests in numerous cities in other parts of the world calling for racial equality for minority and Indigenous groups and a more equitable presentation of their culturally colonised stories. This paper surveys this global uprising exploring its precipitous momentum at a time where most of the world was in lockdown or in forced confinement. Included is how the protests, highlighting deep-rooted underlying social and cultural angst, may have far-reaching impacts in influencing post-pandemic recovery mechanisms in favour of more inclusive communities - a goal ironically embedded in the United Nations' Sustainable Development Goal (SDG) 11 that seeks to 'Make cities inclusive, safe, resilient and sustainable'.
Keywords: 330; George Floyd; Black lives matter; COVID-19; Coronavirus; Urban recovery mechanisms; Inclusivity; Pandemic; Lockdown; Sustainable development goal 11